Lipid Profile dan Tekanan Darah pada Wanita Dewasa Berdasarkan Pemeriksaan BMI dan LP - Yunus Elon; Denny Paul Ricky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to analyze the relationship between BMI, WC (waist circumference) with lipid profile, and blood pressure. The research design uses quantitative methods, with a correlational descriptive approach. The results showed that the mean BMI of respondents was 28.58 or obesity and waist circumference 91.53 were in the high category. At the same time, systolic and diastolic blood pressure were included in hypertension grade 1, with values ​​of 139.05 and 89.03 mmHg. Lipid profile (total cholesterol and triglycerides are within normal limits with a mean of 183.08 and 94.93 mg/dl. Bivariate analysis of BMI and LP with systolic blood pressure and lipid profile with p-value> .05 and p-value <.05 for BMI and LP on diastolic blood pressure Conclusion, There is a significant relationship between BMI and LP on diastolic blood pressure, but there is no meaningful relationship to systolic blood pressure and lipid profile. Keywords: BMI, Waist Circumference, Lipid Profile, Blood Pressure